Water tank’s safety alarm / Ahmad Khadri Abdullah and Shamsui Zakri Zulkifli - Abdullah, Ahmad Khadri; Zulkifli, Shamsui Zakri (2000)
Why we need water level alarm? Water is some important thing which is useful for especially human in the world. Some of country has less water supply give their citizens problem. They may get some disease like cholera because some of them don’t have better and clean water supply. It is so different with us, live in the country which have rich of clean water supply and save for us to use. Because of that we must be thankful to our God because we was given the special gift and it is valuable. But it is so sad to us because there still have some that don’t care about water and they always waste water on the useless way. Some water is wasted under our estimate. The common way the water waste, by the leaking of supplying pipe, and sometimes water is wasted where there have some problem in whatever types of water tank like failure of the tank’s buoy can make the water flow up extremely the and water in the tank will flow out. Some of the water tank was put in outside or the place which seldom the house owner passed by some water tank by especially in flat house, the tank is high at top of the buildings roof. If something happened with their tank they don’t realized it until they see it their own self. We don’t know how much water was wasted before the house owner realized his water was over flowing. Because of this we got an idea in creating this water tank a safety alarm, why not we use in our houses water tank, Water Tank Safety Alarm. Water Tank Safety alarm is the circuits that can detect the overflowing water level in our water tank. The water alarm will detect the over flowing water; the siren and flashing lamp will be work on. The flashing lamp circuit and the siren is the fast way to us for detecting the overflow of water because here we use the sound sense and light (eye). The speaker or buzzer and the lamp, we can put it at the place where easier for us to hear the speaker or buzzer’s sound and see the light flashing.